Health behaviors and goal setting among Karen youth. Issue 4 (28th November 2019) - Danner, Christine; Freeman, Katie; Friedrichsen, Samantha; Brandenburg, Dana
Abstract : Purpose: The purpose of this paper is to describe and compare the health behaviors of Karen youth with that of the other subpopulation seen at a Minnesota clinic. Design/methodology/approach: Demographic information and data on health status, recommended health behaviors and goal-setting patterns were collected via a review of the medical records of patients seen at a family medicine residency clinic in St Paul, Minnesota during a one-year period (July 2015–June 2016). Data were summarized using descriptive statistics. Data on Karen patients were compared with data on other populations. Findings: The study included 765 youths aged 3–17 years. The Karen youth in the study engaged in recommended health behaviors more frequently than their peers on almost every measure. There were statistically significant differences in the amount of sleep, intake of fruits and vegetables, screen time, number of active days per week and consumption of sugar-sweetened drinks between the Karen and their peers overall. Karen youth also reported consuming fewer sweets and fried or processed food than their peers, and they had lower BMI percentiles than other youth. Research limitations/implications: The study relied on participant self-report, which is subject to potential inaccuracies in recall and reporting. Originality/value: To the authors' knowledge, this is the first study detailing health behaviors of Karen youth in the USA. The findings suggest a window of opportunity to support and empower Karen families to maintain healthy habits in order to prevent the development of chronic disease in this community.